Staff perceptions of family access and visitation policies in Australian and New Zealand intensive care units: The WELCOME-ICU survey. Issue 4 (July 2022) - Bailey, Rachel L.; Ramanan, Mahesh; Litton, Edward; Yan Kai, Nathalie Ssi; Coyer, Fiona M.; Garrouste-Orgeas, Maite; Tabah, Alexis; Doyle, Elizabeth; Yarad, Elizabeth; Masters, Kirsty; McGlion, Elaine; et al.
Abstract: Background: Family-centred critical care recognises the impact of a loved one's critical illness on his relatives. Open visiting is a strategy to improve family satisfaction and psychological outcomes by permitting unrestricted or less restricted access to visit their family member in the intensive care unit (ICU). However, increased family presence may result in increased workload and a risk of burnout for ICU staff. Objectives: The objective of this study was to evaluate ICU staff perceptions regarding visiting hours and family access in Australian and New Zealand ICUs. Secondary outcomes included an evaluation of current visiting policies, witnessed events in ICUs, and barriers to implementing open visiting policies. Design: A web-based survey open to all healthcare workers in Australia and New Zealand ICUs was distributed through local, state-based, and national critical care networks. Open visiting was defined as ICUs open for visiting >14 h per day. Main results: We received 1255 valid responses. Most respondents were nurses (n = 930, 74.1%) with a median critical care experience of 10 y. Most worked in open visiting ICUs (n = 749, 59.7%). Reported visiting hours varied greatly with a median of 20 h per day (interquartile range: 10–24 h). Open visiting was perceived as beneficial for the relatives, but less so for patients and staff (relatives: n = 845, 67.3%, patients: n = 561, 44.7%, staff: n = 257, 20.5%, p < 0.0001). Respondents from closed visiting units and nurses identified more risks from open visiting than other professional groups. Generally, staff preferred not to change from their current practice. Conclusion: We report that staff perceived open visiting as beneficial for relatives, but also identified risks to themselves, including increased workload, a risk of burnout, and a risk of occupational violence. Reluctance to change highlights the importance of addressing staff perceptions when implementing an open visiting policy.